1993
DOI: 10.1159/000147438
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the Standardbred Trotter Measured at 6, 7, 8 and 9 m/s on a Treadmill, before and after 5 Months of Prerace Training

Abstract: A kinematic study was performed on a group of 8 Standardbred stallions. Recordings were done using a modified CODA-3 optoelectronic kinematic analysis system with the horses running on a treadmill at speeds of 6, 7, 8, or 9 m/s. Linear and temporal gait characteristics, joint angle diagrams and the trajectories of the hoof in a plane perpendicular to the direction of movement were studied. Two consecutive recording sessions were held at an age of 21–23 months, and a third was held 5 months later after an inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 4 publications
5
25
0
1
Order By: Relevance
“…The increase in axial muscle activity (Sp, LD, RA) provides additional trunk stability and changes the spine into a rigid platform from which the limbs may swing faster (Rooney 1982) and generate more propulsive force. This study demonstrates that most of the kinematic changes observed at increased speed in previous studies (van Weeren et al 1993;Back et al 1996) are associated with increased muscle activity. It tends to confirm that speed training could be beneficial in developing the musculature of the horse, but could also increase the risk of muscle stiffness.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The increase in axial muscle activity (Sp, LD, RA) provides additional trunk stability and changes the spine into a rigid platform from which the limbs may swing faster (Rooney 1982) and generate more propulsive force. This study demonstrates that most of the kinematic changes observed at increased speed in previous studies (van Weeren et al 1993;Back et al 1996) are associated with increased muscle activity. It tends to confirm that speed training could be beneficial in developing the musculature of the horse, but could also increase the risk of muscle stiffness.…”
Section: Discussionsupporting
confidence: 68%
“…Both collected and extended trots are supposed to be beneficial for the animal. In horses as well as in man, subject velocity is known to affect stride parameters (Leach and Drevemo 1991;Rooney et al 1991;Clayton 1994), ground reaction forces (McLaughlin et al 1996) or limb movements (van Weeren et al 1993;Holmström et al 1995). It has also been demonstrated in previous studies that speed has a significant effect on the level and duration of excitation of several muscles in horses at trot (Robert et al 2000(Robert et al , 2001a.…”
Section: Introductionmentioning
confidence: 88%
“…Foot impact excites the equine limb to vibrate in a cranio-caudal direction at a frequency of 30-40 Hz (Fig. 2) 15 . The vibrations are similar on different surfaces (tarmac 35.9 ± 1.2 Hz; concrete 35.8 ± 2.1 Hz; rubber matting 34.9 ± 1.2 Hz; n = 8), and correspond to a muscle-tendon unit length change of about 2 mm (from joint angle changes) and an energy of 4-8 J.…”
mentioning
confidence: 99%
“…This is unfortunate, since gait is such an important part of equine health and performance. Also, it has been well established that equine gait is very reproducible and is fixed at an early age (van Weeren et al 1993), indicating that gait analysis may identify small gait abnormalities as clinically relevant.…”
Section: Editorialsmentioning
confidence: 99%